Food systems with integral and semi-integral diets, made with sugar cane forage (Saccharum officinarum): its effect on viscera morphometry and internal organs of crossbred Holstein bulls. - Rodríguez, Duniesky; Tuero, O.; Hernández, J. L.; Sarduy, Lucía (Cuban Journal of Agricultural Science, 2016)
A total of 10 stabulated crossbred Holstein bulls were selected, to evaluate food systems effect, with integral and semi- integral diet, in viscera and internal organs weight. The average live weights were 428 and 437kg, respectively, for treatments: A) sugar cane forage+ molasses-urea 2%+ concentrate (mixed as integral diet) and B) sugar cane forage+ molasses-urea 2%(mixed) +concentrate (separately feeding trough). Animals were weighed before moving them to the slaughter house and left to fast for 24h, with ad libitum water. Later they were slaughtered through the captive bolt method. Internal organs and fifth quarter components were separately weighed. A simple classification analysis was carried out. There was not significance difference between treatments for slaughter weight, head, hide, full and empty digestive system and legs. There was an increase (P < 0.05) of heart weight and the percentage regarding the live weight of the animals consuming semiintegral diet, regarding to the ones that consuming the integral diet, with values of 1.6- 1.2kg and 0.5- 0.45 for each treatment, respectively. It is concluded that the animals that consuming semi-integral diet showed a higher heart weight and percentage regarding the empty body weight, than the ones that consuming integral diet. Key words: bovine cattle, internal organs, sugar cane, fifth quarter